Durvalumab induced sarcoid‐like pulmonary lymphadenopathy. Issue 3 (25th February 2020) - Sanderson, Emma; Wimaleswaran, Hari; Senko, Clare; White, Shane; McDonald, Christine F.
Abstract: Immune checkpoint inhibitors (ICIs) have become pivotal in the treatment of lung cancer. An increasing number of immune‐related adverse events (irAEs) have been recognized with their use. To our knowledge, this is the first published case of sarcoid‐like pulmonary lymphadenopathy associated with durvalumab, a monoclonal antibody against programmed death ligand‐1 (PD‐L1). A 76‐year‐old woman received adjuvant durvalumab for Stage IIA pT2aN1M0 (American Joint Committee on Cancer, Seventh edition) poorly differentiated lung adenocarcinoma. After three cycles, a sarcoid‐like granulomatous reaction was identified in mediastinal and hilar lymph nodes. Although the lymphadenopathy remained stable in size with the ongoing treatment, progressive intracranial metastases were identified after a further three cycles of durvalumab. Sarcoid‐like inflammation with the formation of non‐caseating granulomas in the absence of systemic sarcoidosis is an irAE which may mimic disease progression. Although a subset of patients who experience this reaction may have a favourable response to checkpoint inhibition, progression of disease may occur contemporaneously. Abstract : Immune checkpoint inhibitors, such as durvalumab, are associated with a variety of unique immune‐related adverse events. In this case, sarcoid‐like mediastinal and hilar lymphadenopathy developed with the use of adjuvant durvalumab for the treatment of lung adenocarcinoma.